APLIKASI METODE ARDRA DALAM IDENTIFIKASI ISOLAT Bacillus thuringiensis ENDOGENIK SEBAGAI PENGENDALI HAMA KUBIS (Crocidolomia binotalis) - Salaki, Christina L.; Sembiring, Langkah (Universitas Sam Ratulangi, 2011)
ABSTRACT Indonesian indigenous bacterial isolates of B. thuringiensis pathogenic to cabbage pest (C. binotalis) were molecularly characterized and identified using DNA fingerprinting method of ARDRA (Amplified Ribosomal DNA Restriction Analysis). Chromosomal DNA of 10 selected isolates (SLK2.3, SRNG4.2, TKO1, TK9, YPPA1, UG1A, BLPPN8.2, YWKA1, BAU3.2, LPST1) and 2 reference strains (B. thuringiensis serovar kurstaki HD1 & B. thuringiensis serovar israelensis H14) were isolated and purified by standard method. 16S rRNA genes were amplified by PCR method using universal primers of 27f and 1529r. PCR products were digested by 4 restriction endonucleases (EcoR1, HindIII, Pst1 dan HaeIII), and separated by agarose electrophoresis method to generate ARDRA profiles. Results of study showed that only ARDRA profiles generated by Hae III digestion were found to be meaningful and therefore used to identify the isolates. The ARDRA profile analysis indicated that the reference strain of B. thuringiensis serovar kurstaki HD1 could be clearly separated with B. thuringiensis serovar israelensis H14. In fact, those two strains have been widely recognized to be different in terms of their pathogenic specifity against insects. B. thuringiensis serovar kurstaki HD1 has been known to be specifically pathogenic to Lepidopteran whereas B. thuringiensis serovar israelensis H14 has been known to be specifically pathogenic to Dipteran. Key words : application, ARDRA, indigenous, B. thuringiensis, C. binotalis Â